Molecular epidemiology of severe respiratory disease by human rhinoviruses and enteroviruses at a tertiary paediatric hospital in Barcelona, Spain. (August 2015) - Launes, C.; Armero, G.; Anton, A.; Hernandez, L.; Gimferrer, L.; Cisneros, C.; Jordan, I.; Muñoz-Almagro, C.
Abstract: In order to describe the molecular epidemiology of human rhinovirus (HRV) and enterovirus (EV) infection in severely ill children, we studied all episodes of bronchospasm/bronchopneumonia in 6-month-old to 18-year-old patients from January 2010 to May 2012 who required mechanical ventilation. HRV/EVs were detected in 55 (57.3%) of 96 patients, of which 50 (91%) were HRV (HRV-A, 16; HRV-B, 1; HRV-C, 18) and 5 (9%) were EVs (EV-D68, 3). No significant differences in epidemiologic and clinical characteristics were found between different types. In six of the 13 patients who required invasive mechanical ventilation, HRV was the only pathogen detected.